In vitro antimicrobial, antioxidant, haemolytic, thrombolytic activities and phytochemical analysis of Cipadessa bacifera leaves extracts - T Thirunavukarasu; K Santhana Lakshmi; M Tamilarasan; S Sivamani; D Sangeetha; TP Rajesh (International Journal of Phytomedicine, 2014)
Objective: To study the leaves of Cipadessa bacifera for their antimicrobial, antioxidant, haemolytic, thrombolytic activities and to perform phytochemical evaluation. Methods: The three extracts (methanol, cyclohexane, chloroform) of Cipadessa bacifera were screened for antimicrobial activity against eight pathogenic microorganisms by well diffusion method. In vitro antioxidant activity of extract was studied using hydrogen peroxide radical scavenging assay. The haemolytic activity was determined using agar diffusion techniques on blood agar plate, thrombolytic activity by clot disruption and phytochemical potential by qualitative analysis. Results: Among the different extracts tested, the methanol extract of leaves showed significant antimicrobial activities. The most susceptible micro-organisms were found to be Gram negative bacteria (Sphingomonas, Klebsiella pneumoniae, Citrobacter), Gram positive bacteria (Enterococcus faecalis) and fungai (Candida albicans). H2O2 scavenging activity of Cipadessa bacifera was found to increase with increasing concentration of the extract. IC50 values of H2O2 scavenging activity was 100.92±0.41 µg/mL which was found in cyclohexane extract. The haemolytic activity was found to be higher in chloroform extract than methanol, cyclohexane and the methanol extract shows 14.63 % clot lytic whereas standard streptokinase shows 30.86 % clot lytic activity in thrombolytic assay. The phytochemical evaluation indicates the presence of chemical constituents. Conclusions: This study shows that the methanol and chloroform extract of leaves of Cipadessa bacifera has bioactivity but further compound isolation is necessary to confirm the activities of individual compound.